Struktura wieloznaczności poznawczej (na podstawie komunikowania w polityce) - Dobrosz-Michiewicz, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper presents ambiguity phenomena in terms of cognitive categorization and blending processes. Politicians’ manifesto speeches are analysed based on Lakoff’s and Langacker’s semantics and Langacker’s grammar research investigation, resulting in describing ambiguity phenomena more as the sender’s or receiver’s mental concepts than as a linguistic property of the message. Moreover, cognitive points of view in the research on ambiguity reveals its multileveled nature due to the polysemic nature of mental categories or blends.